정치적 행위로서의 공동체 번역에 관한 시론적 연구: ‘사회 연결 모델’의 ‘책임’ 개념을 중심으로 - 강지혜; 김경혜; 유한내 (번역학연구, 2019)
This study examines the relationship between political responsibility and the practice of community translation from the perspective of Iris Marion Young’s ‘social connection model’ (Young 2006). According to Young, all agents connected to global structural injustice bear political responsibility, which is shared, non-blameworthy, and forward-looking. By extension, political responsibility must be taken up collectively by all participants in order to effectively promote change. Political responsibility is a crucial notion to account for the collective actions of volunteers translating in the context of non-profit organizations committed to linguistic diversity and multilingualism. We argue that when volunteer translators’ activities are embedded in communities dedicated to promoting linguistic justice or intervening in the unequal distribution of knowledge, translation is an act of political responsibility. The study underlines the need for further investigations of the relationship between community translation and politics of responsibility.
Keywords: 공동체 번역; 사회 연결 모델; 책임; 지식의 생산과 확산; 언어적 (부)정의; community translation; social connection model; responsibility; knowledge production and distribution; linguistic (in)justice